2020
DOI: 10.1002/edn3.141
|View full text |Cite
|
Sign up to set email alerts
|

Environmental DNA shedding and decay rates from diverse animal forms and thermal regimes

Abstract: Environmental DNA (eDNA) analysis from water samples is a promising new method to identify both targeted species and whole communities of aquatic organisms. However, the current literature regarding eDNA shedding rates primarily focuses on fish and most decay rate constants are reported for warm sunlit waters. Here, we conducted experiments to investigate how eDNA shedding differs between animal forms and how long eDNA can persist in waters of varying temperature and light conditions. We designed quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
143
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(155 citation statements)
references
References 85 publications
(93 reference statements)
12
143
0
Order By: Relevance
“…In summary, these results demonstrate how incorporating eRNA quantification into existing eDNA protocols can both increase detection probability by targeting highly concentrated rRNAs and improve interpretation of positive detections by modeling the ratio of eRNA:eDNA, or assessing detection of low abundant mitosisassociated mRNAs. The release and degradation relationships between genomic fragments found here might change due to physiological differences between life-histories 51 or between organisms 19 , and thus these genomic relationships should be investigated for other taxonomic groups. We found a significant decrease in the Ratio R:D over time, allowing us to predict the age of genomic material, and thus reduce error from legacy genomic signal.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In summary, these results demonstrate how incorporating eRNA quantification into existing eDNA protocols can both increase detection probability by targeting highly concentrated rRNAs and improve interpretation of positive detections by modeling the ratio of eRNA:eDNA, or assessing detection of low abundant mitosisassociated mRNAs. The release and degradation relationships between genomic fragments found here might change due to physiological differences between life-histories 51 or between organisms 19 , and thus these genomic relationships should be investigated for other taxonomic groups. We found a significant decrease in the Ratio R:D over time, allowing us to predict the age of genomic material, and thus reduce error from legacy genomic signal.…”
Section: Discussionmentioning
confidence: 98%
“…The decay rates of the exponential decay models were estimated as dC′/dt = − kC′, where C′ = C t /C 0 was used to normalize eDNA/eRNA concentration. Previous decay studies have demonstrated biphasic eDNA decay 19,37 , and as such we analyze the log-linear decay rates over the initial 72-h. The decay rates were estimated by fitting a linear mixed-effect model with the values of log e (C t /C 0 ) as the response variable.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, our findings strongly reinforce the conclusion that eDNA can discriminate communities at fine spatial scales as first established by Port et al 27 , even within habitats. Fish abundance estimated from eDNA data depends on several factors, including eDNA shedding, degradation and dispersion [45][46][47][48] . The persistence of eDNA can vary among aquatic organisms, but a growing body of evidence suggest that eDNA decay rates are faster in marine compared to freshwater environments and that once shed eDNA may only be detectable for hours to a few days [46][47][48] .…”
Section: Taxa Richnessmentioning
confidence: 99%
“…Fish abundance estimated from eDNA data depends on several factors, including eDNA shedding, degradation and dispersion [45][46][47][48] . The persistence of eDNA can vary among aquatic organisms, but a growing body of evidence suggest that eDNA decay rates are faster in marine compared to freshwater environments and that once shed eDNA may only be detectable for hours to a few days [46][47][48] . For instance, both Andruszkiewicz et al 47 and Collins et al 46 compiled previous findings on eDNA half-lives, showing they were relatively short in temperate marine environments, ranging from 6.9 h for the northern anchovy 45 to 63 h for the Maugean skate 49 .…”
Section: Taxa Richnessmentioning
confidence: 99%
See 1 more Smart Citation